Strategy for Implementing Climate Smart Agriculture Technology in Rice Farming in Karang Agung Ilir Subdistrict, Banyuasin Regency - Efraini, Efraini; Purba, Yudhi Zuriah Wirya; Thanomutiara, Eka; Firmansyah, Arie (Kadiri University - Faculty of Agriculture, 2024)
The CSA approach is an approach to developing agricultural strategies to maintain sustainable food security in facing the impacts of climate change. This research aims to formulate strategies to implement Climate Smart Agriculture (CSA) technology in Karang Agung Ilir District, Banyuasin Regency. In this research, the method used is SWOT analysis. A tool that can be used to formulate a strategy is the SWOT matrix. This matrix will describe the strengths and weaknesses (internal) of farming businesses that apply CSA technology in Karang Agung Ilir District, Banyuasin Regency. This matrix can produce four sets of possible strategic alternatives, namely S-O Strategy, W-O Strategy, S-T Strategy and W-T Strategy. The research results using SWOT analysis have formulated a strategy based on internal and external factors as follows: (1) The strategy falls into quadrant I, indicating the presence of strengths and opportunities to support aggressive growth policies. This situation is highly favourable because some opportunities and advantages can be utilized: (2)Maximizing resources, facilities, and infrastructure, as well as government support, in implementing CSA technology; (3)Providing regular mentoring programs to farmers and extension services to enhance their knowledge and skills in implementing the CSA program; (4)Strengthening farmer institutions to provide them with accessibility to technological devices and continuous innovation information in the implementation of CSA technology.